1996
DOI: 10.1007/bf01736992
|View full text |Cite
|
Sign up to set email alerts
|

Positive thyroid cancer scintigraphy using technetium-99m methoxyisobutylisonitrile

Abstract: The aim of the study was to evaluate the possibility of detecting thyroid cancer recurrences without the need for withdrawal of thyroid suppressive treatment. Upper-body or whole-body scintigraphy was performed in a group of 200 patients evaluated for differentiated thyroid cancers in 1993 and 1994 using technetium-99m sestamibi. Scans were performed 20-30min following i.v. administration of 500MBq of 99mTc-methoxyisobutylisonitrile (MIBI). Bone and lung metastases were detected with very high sensitivity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 3 publications
0
9
1
2
Order By: Relevance
“…Another factor for their low sensitivity might be the delayed image acquisition time, because we previously found that 99mTc-MIBI accumulation observed in the early image (10-30 minutes) disappeared at the delayed scan (3 hours) in 8 of 13 patients with lung métastases and 5 of 11 bone metastases (14). However, Nemec et al (12) reported high sensitivity for bone (100%; 17/17) and lung (94.7%; 18/19) Compared with the studies by Nemec et al (12), we had lower sensitivity (78.4%; 40/51) for lung métastases, which appears attributable to the small size of lesions (<1.0 cm).…”
Section: Discussioncontrasting
confidence: 66%
See 3 more Smart Citations
“…Another factor for their low sensitivity might be the delayed image acquisition time, because we previously found that 99mTc-MIBI accumulation observed in the early image (10-30 minutes) disappeared at the delayed scan (3 hours) in 8 of 13 patients with lung métastases and 5 of 11 bone metastases (14). However, Nemec et al (12) reported high sensitivity for bone (100%; 17/17) and lung (94.7%; 18/19) Compared with the studies by Nemec et al (12), we had lower sensitivity (78.4%; 40/51) for lung métastases, which appears attributable to the small size of lesions (<1.0 cm).…”
Section: Discussioncontrasting
confidence: 66%
“…Because 99mTc-MIBI enters skeletal muscle tissue by passive diffusion, muscle perfusion abnormalities such as peripheral artery disease (20), muscle diseases, and removal of muscles after extensive operation for thyroid cancer may cause asymmetric appearance and also false-positive scans. Nemec et al (12) reported 39 false-positive sites including 27 in the neck, 9 in the lung, and 3 in the bone, and suggested that false-positive uptake may have occurred in scars after previous treatment of primary tumors and their métastases. However, they did not describe other causes of false-positive results.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The precise role of this agent in assessing patients with thyroid cancer has yet to be determined. Available evidence indicates that, like 201T1, 99mjc sestamibi may be useful in localizing recurrent thyroid carcinoma in 131I-negative patients in whom there is other evidence of recurrence (47)(48)(49)(50). Because of the 6-h half-life of 99mTc, allowing the administration of 20-25 mCi (740-925 MBq), and its more suitable photon energy for imaging, 99mTc sestamibi produces images of higher quality than 201T1.…”
Section: Radiopharmaceuticals Other Than Radioiodinementioning
confidence: 97%